Information of scientific and training facility at Academician V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs - art Editor (Вестник трансплантологии и искусственных органов, 2011)
Information of scientific and training facility at Academician V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs